Factors affecting Children’s (1-13 Years) Oral Health: A Case Study of Buhara Sub-County, Kabale District. - Ainamani , Joan (Student’s Journal of Health Research Africa, 2022)
Background Oral health is of vital importance to general health in humans. Caries occurs in both developed and developing countries. Despite the marked improvement in oral health, it is still widespread among children and it can be controlled but not eliminated. Objectives The broad objective was to assess the factors affecting children’s (1-13 years) oral health: a case of Buhara sub-county, Kabale District. The specific objectives included; assessing the knowledge of caregivers, identifying the attitude of caregivers, and establishing the practices of caregivers towards children’s oral health: a case of Buhara sub-county, Kabale District. Methodology The study was carried out using a descriptive cross-sectional design and it involved a sample size of 73 respondents. The data was collected using self-administered questionnaires analyzed by Microsoft excel software and presented in frequency tables, figures, and statements. Results The study found that (72.60%) did not know about oral health,(and 41.10% )of the respondents knew that diet especially sugary food consumption mainly caused dental problems. (17.81%) of the respondents agreed that the rotten child’s tooth causes psychological torture. Conclusion The knowledge of the caregivers about children’s (1-13 years) oral health was poor since the majority of the respondents did not know about children’s oral health. Recommendation There is a great need for health workers to deliver information about oral health to community members who can’t access the health facility.